“We don’t normally require that in other contexts, do we”: Interpersonal meanings of tag questions in British university seminars based on the BASE corpus - Wei, Lifang; Leung, Alex Ho-Cheong; Sun, Yufeng (Frontiers in Psychology, 2023)
This study investigates the interpersonal meanings expressed by English tag questions in the context of British university seminars from two dimensions: evidential modification of tags and conduciveness of responses. The data for the study derive from seminars in the British Academic Spoken English (BASE) Corpus, which is herein both quantitative and qualitative analyzed. The findings reveal that: (1) three-quarters of tag questions in the data are utilized by teachers, and the unmarked form of tag questions in university seminars are generally positive-negative forms, with a few examples of other varieties; (2) regarding evidential modification of tags, depending on the degree of epistemic certainty of the speakers on the proposition of the anchor, the default function of teachers’ tag questions in the data is to convey emphasis, followed by confirmatory function, with only a few cases of informational function; and (3) regarding conduciveness of responses, over 70% of tag questions are followed by no verbal response, while less than 30% are followed by explicit responses. Accordingly, these findings raise the question of whether tag questions can really provide sufficient scope for interactions in classroom. It is hoped that this nuanced, corpus-based analysis of tag question utilization within the context of British university seminars would empirically reveal the interpersonal relations between teachers and students and thereby shed light on more efficient seminar discussions.